The Path for a Hungarian University to Become a Learning Organisation - Réka Barabás; Zsuzsanna Pupp (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Ever since the Lisbon Summit in 2000, the European Comission has treated universities as engines of economic development. The University of the 21st century has to foster an entrepreneurial culture and encourage students to develop entrepreneurial initiative and seek innovation, and university needs to adapt its academic services to to market realities, managing this process. Due to various resasosn, e.g., universities operate supported by state, and could in the same time function as entrepreneurial organisations. However, universities do not have the pressure for performance improvement, as in the market-driven sector, mainly since enrolment is centralized, indicating that university reforms in Hungary are inevitable. Széchenyi István University has maintained and developed a cooperation with Audi Hungaria for the last 20 years which has permitted the establishment of an extended cooperation network in the region with many actors of the economic sector. From this point of view, we analyse the opportunities and needs of Hungarian universities to change, develop and to search for a way for our university to become a successful learning organisation.
Keywords: I23; 330; triple helix; university reforms; entrepreneurial university; learning organisation